The Effect of Some Environmental Conditions on Phytoplanktonic Structure in AL-Diwanyia River - FoÂ´ad M.Alkam; Noor N. AL-Mayalee (Al-Qadisiyah Journal of Pure Science, 2018)
The present study included some physical and chemical characters in AL-Diwnayia river to show the effect these characters on the phytoplanktonic structure , the samples of water were collected at three stations from October 2012 to September 2013 .the first station was lied in the North west of AL-Diwanyia city ,the second station was lied in the center of AL-Diwanyia city and it was remote from first station about 35 KM ,while the third station was lied to the South of AL-Diwanyia city and it was far away from the second station about 13 KM .the characters was including temperature ,pH, turbidity ,electrical conductivity , alkalinity , hardness ,Ca and Mg , ions ,dissolved oxygen ,and BOD5, and nutrient (nitrate , nitrite , phosphate ). The results show that values of temperature air and water , PH, electrical conductivity, turbidity was[ (15-43 )CËš 13-33) CËš ( 7.31-7.82) (1264- 1555) Î¼S/cm (43.6- 59.02) NTU] respectively and the concentration of alkalinity , hardness ,Ca and Mg , ions was [(131.5-227.4)ØŒ( 312.3-458.5)ØŒ(86.4-142)(76.8-54.8)] mg/Respectively and the concentration of dissolved oxygen ,and BOD5 was[ (6.30-8.26ØŒ ) (1.19-3.08)]mg/l respectively ,and the concentrations of nutrients (nitrate , nitrite , phosphate)was[(302.6-558.4) (1.59-3.4),(ND- 2.34)] Ïºg/l , Dominance was to the class Bacillariophyceae then class Chlorophyceae then Cyanophyceae then Euglenophyceae and finally Dinophyceae and the first station was recorded the highest number of species.